Health Financing System in Cameroon at the Crossroads between Beveridge and Bismarck Models: Towards a Hybrid System for Achieving Universal Health Coverage - Fadimatou, Altine; Njoumemi, Zakariaou; Essi, Marie Josee (British Journal of Healthcare and Medical Research, 2025)
Health financing reforms are prioritized high on both political and policy frameworks in many low- and middle-income countries where the approach combines tried and tested features of the two theoretical classic models from Europa namely the Beveridge National Health Service and the Bismarck social insurance. The Beveridge model is tax-funded systems of government-run health financing that can provide free healthcare to all residents of a country or to specific target groups at affordable cost but cannot avoid the risk of delivering low and poor quality health services. The Bismarck model has the potential of achieving high quality health service but cannot offer healthcare for the entire population of a country at an affordable cost. In this perspective, African countries have the opportunities to design conceptual health financing systems which can emerge from the strengths and avoid the pitfalls of the two theoretical existing systems. This study aimed to analyze the health financing model for achieving universal health coverage in Cameroon in the light of existing theoretical models. A scoping review method was used for data collection and analysis. The results showed that given the respective principles defining the Beveridgean and Bismarckian models along with their strengths and pitfalls, the hybrid model which is combining the two classic models can stand as the best opportunity of mobilizing sustainable financing for achieving universal health coverage in the country. Cameroon adopts a hybrid model of health financing, characterized by a gradual shift from the Beveridgian model to a mixed approach incorporating Bismarckian tools, while retaining specific features linked to the national socio-economic and governance context. However, the Beveridgean and Bismarckian health financing models have strong arguments of strengths in favor as well as weaknesses usually used against them. The hybrid model combines the best features of Bismarck and Beveridge models started with a system financed mainly by taxes and progressively move the spectrum of almost full tax finance to integrate the component of social insurance for universal health coverage in the national health system. The policy implications pointed out that any single theoretical model cannot provide universal affordable services and population coverage. Achieving universal health coverage should require a hybrid tripartite based combination of two classic Beveridge and Bismarck models involving tax funding for public finance and social insurance by employers and employees as well as mobilizing private insurance and innovative domestic financing sources. Keywords: Health financing, Beveridgian model, Bismarckian model, hybrid system, universal health coverage, Cameroon.